External and Internal Conjunctions in the News Story Text of the Jakarta Post - Novita Sari; Amrin Saragih; Anni Holila Pulungan (Universitas Negeri Medan, 2020)
This study was investigated external and internal conjunctions in the news story text of the Jakarta Post based on Systemic Functional Linguistics Approach. The objective of this study was to describe the realization of external and internal conjunctions. The research was conducted by using qualitative design. The data of this research were clause complex of external and internal conjunctions in the news text the Jakarta Post. The data were taken from website official Jakarta Post https://www.thejakartapost.com/. The data were collected by documentary technique. The technique of data analysis applied interactive model technique by Miles, Huberman and Saldana (2014). The findings showed external and internal conjunctions describes in clause complex news text used to clause complex have several clauses consist of independent clause is an equal (paratactic) and clause complex have several clauses consist of independent clause relate with dependent clause is an unequal (hypotactic). Keywords: External Conjunction, Internal Conjunctions, News Text